Effects of Macroporous Resin Extract of Dendrobium officinale Leaves in Rats with Hyperuricemia Induced by Fructose and Potassium Oxonate - Wang, Yu-Zhi; Zhou, Cong; Zhu, Li-Jie; He, Xing-Li-Shang; Li, Lin-Zi; Zheng, Xiang; Xu, Wan-Feng; Dong, Ying-Jie; Li, Bo; Yu, Qiao-Xian; Lv, Gui-Yuan; Chen, Su-Hong (Combinatorial Chemistry & High Throughput Screening, 2022)
Aims and Objectives: Fructose, as a ubiquitous monosaccharide, can promote ATP consumption and elevate circulating Uric Acid (UA) levels. Our previous studies have confirmed that the macroporous resin extract of Dendrobium officinale leaves (DoMRE) could reduce the UA level of rats with hyperuricemia induced by a high-purine diet. This study aimed to investigate whether DoMRE had a UA-lowering effect on rats with hyperuricemia caused by fructose combined with potassium oxonate, so as to further clarify the UA-lowering effect of DoMRE, and to explore the UAlowering effect of DoMRE on both UA production and excretion. Materials and Methods: Rats with hyperuricemia induced by fructose and potassium oxonate were administered with DoMRE and vehicle control, respectively, to compare the effects of the drugs. At the end of the experiment, the Serum Uric Acid (SUA) and Creatinine (Cr) levels were measured using an automatic biochemical analyzer, the activities of xanthine oxidase (XOD) were measured using an assay kit, and the protein expressions of Urate Transporter 1 (URAT1), glucose transporter 9 (GLUT9), and ATP-Binding Cassette Superfamily G member 2 (ABCG2) were assessed using immune-histochemical and western blot analyses. Hematoxylin and eosin staining was used to assess the histological changes in the kidney, liver, and intestine. Results: Fructose and potassium induced hyperuricemia in rats. Meanwhile, the activities of XOD were markedly augmented, the expression of URAT1 and GLUT9 was promoted, and the expression of ABCG2 was reduced, which were conducive to the elevation of UA. However, exposure to DoMRE reversed these fructose- and potassium oxonate-induced negative alternations in rats. The activities of XOD were recovered to the normal level, reducing UA formation; the expressions of URAT1, ABCG2, and GLUT9 returned to the normal level, resulting in an increase in renal urate excretion. Conclusion: DoMRE reduces UA levels in rats with hyperuricemia induced by fructose combined with potassium oxonate by inhibiting XOD activity and regulating the expression of ABCG2, URAT1, and GLUT9. DoMRE is a potential therapeutic agent for treating hyperuricemia through inhibiting UA formation and promoting UA excretion.
Keywords: Dendrobium officinale leaves